2022
DOI: 10.3390/app12010498
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope and Radiocarbon Analysis for Diet, Climate and Mobility Reconstruction in Agras (Early Iron Age) and Edessa (Roman Age), Northern Greece

Abstract: In this article we present an isotopic analysis of human bone collagen (δ13Ccol, and δ15Ncol) and bone apatite (δ13C) for diet reconstruction, as well as δ18Oap of human bone apatite for climate reconstruction, using samples from Northern Greece. Radiocarbon dating analysis was conducted on three of the Agras samples and the results (from 1000 to 800 BC) correspond to the Early Iron Age. Isotopic values for δ13Ccol range from −20.5‰ to −16‰ and for δ15Ncol from 6‰ to 11.1‰—a strong indication of a C3-based die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The utilization of both 𝛿 13 C coll and 𝛿 13 C carb in isotopic studies, therefore, provides a more holistic estimate of several dietary inputs. In Europe, some studies have made use of both components (Dotsika et al, 2022 ; Etu‐Sihvola et al, 2022 ; Grupe et al, 2009 ; Gugora et al, 2022 ; Olsen et al, 2016 ; Reitsema et al, 2010 ; Toyne et al, 2022 ; Yoder, 2012 ; Zechini et al, 2021 ). Although 𝛿 13 C coll data from these studies suggested that dietary protein was primarily derived from C 3 resources, the differences in the 𝛿 13 C carb values among the individuals at certain sites indicated that some individuals may have consumed more C 4 or marine foods than others (Dotsika et al, 2022 ; Reitsema et al, 2010 ; Yoder, 2012 ), demonstrating the utility of analyzing 𝛿 13 C carb alongside 𝛿 13 C coll values.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of both 𝛿 13 C coll and 𝛿 13 C carb in isotopic studies, therefore, provides a more holistic estimate of several dietary inputs. In Europe, some studies have made use of both components (Dotsika et al, 2022 ; Etu‐Sihvola et al, 2022 ; Grupe et al, 2009 ; Gugora et al, 2022 ; Olsen et al, 2016 ; Reitsema et al, 2010 ; Toyne et al, 2022 ; Yoder, 2012 ; Zechini et al, 2021 ). Although 𝛿 13 C coll data from these studies suggested that dietary protein was primarily derived from C 3 resources, the differences in the 𝛿 13 C carb values among the individuals at certain sites indicated that some individuals may have consumed more C 4 or marine foods than others (Dotsika et al, 2022 ; Reitsema et al, 2010 ; Yoder, 2012 ), demonstrating the utility of analyzing 𝛿 13 C carb alongside 𝛿 13 C coll values.…”
Section: Introductionmentioning
confidence: 99%
“…Bioarcheological data regarding the health status of Roman Macedonian populations within the territory of modern Greece are extremely scarce. To date, there are merely six relevant studies; Malama and Triantaphyllou (2003) examined the biological and paleopathological profile of an assemblage from Amphipolis; Papageorgopoulou et al (2009) presented a case study of embalming from Thessaloniki; Michael and Dotsika (2017), Dotsika and Michael (2018), and Dotsika et al (2022) performed isotopic analysis on individuals from Edessa; and, finally, Vergidou et al (2021) addressed issues related to dental health and diet in the community of Pontokomi‐Vrysi. These studies highlight the important role bioarcheology can play in an area where many aspects of its social history, especially that of the lower classes, remain unknown due to the lack of adequate historical and textual evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Bioarcheological data regarding the health status of Roman Macedonian populations within the territory of modern Greece are extremely scarce. To date, there are merely six relevant studies; examined the biological and paleopathological profile of an assemblage from Amphipolis; Papageorgopoulou et al (2009) presented a case study of embalming from Thessaloniki; , Dotsika andDotsika et al (2022) performed isotopic analysis on individuals from Edessa; and, finally, addressed issues related to dental health and diet in the community of Pontokomi-Vrysi. These studies highlight the important role bioarcheology can play in an area where many aspects of its social history, especially that of the lower classes, remain unknown due to the lack of adequate historical and textual evidence.…”
Section: Introductionmentioning
confidence: 99%